2016
DOI: 10.1016/j.fertnstert.2015.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes decline with increasing recipient body mass index: an analysis of 22,317 fresh donor/recipient cycles from the 2008–2010 Society for Assisted Reproductive Technology Clinic Outcome Reporting System registry

Abstract: Success rates in recipient cycles are highest in those with low and normal BMI. Furthermore, there is a progressive and statistically significant worsening of outcomes in groups with higher BMI with respect to clinical pregnancy and live birth rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
5
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(53 citation statements)
references
References 25 publications
3
43
5
2
Order By: Relevance
“…However, the difference recorded among patients with a BMI of at least 30 was statistically significant ( P =0.024). The results of the study are consistent with previous studies …”
Section: Pregnancy Ratessupporting
confidence: 93%
See 1 more Smart Citation
“…However, the difference recorded among patients with a BMI of at least 30 was statistically significant ( P =0.024). The results of the study are consistent with previous studies …”
Section: Pregnancy Ratessupporting
confidence: 93%
“…The results of the study are consistent with previous studies. [2][3][4] The present study demonstrated an inverse relationship between increasing BMI and pregnancy rate in patients with infertility. With increasing obesity prevalence worldwide, and especially in the gulf region, pre-conception counseling and weight loss are highly recommended before using assisted conception methods to optimize outcomes.…”
supporting
confidence: 61%
“…Two large retrospective reviews have utilized this design. The largest examined the 2008–2010 SART Registry, and included 22,317 donor oocyte cycles (154). Recipients with BMIs between 30–34.9 kg/m 2 had a lower implantation rate than normal range (BMI 18.5–24.9 kg/m 2 ) patients (42.6% vs. 49.3%, p<0.001).…”
Section: The Effect Of Systemic Factors On Implantation After In Vitrmentioning
confidence: 99%
“…It is known that obesity is associated with negative outcomes in obstetrics [15], regardless of method of conception, perhaps due to derangement of the HPO axis, oocyte quality, and receptivity of the endometrium. Studies have shown that obese women who lose at least 10% of their body weight have better pregnancy outcomes than those who do not [15,16].…”
Section: Discussionmentioning
confidence: 99%